Grammar and cognition : dualistic models of language structure and language processing - Haselow, Alexander; Kaltenböck, Gunther (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2020)
"This volume brings together linguistic, psychological and neurological research in a discussion of the Cognitive Dualism Hypothesis, whose central idea is that human cognitive activity in general and linguistic cognition in particular cannot reasonably be reduced to a single, monolithic system of mental processing, but that they have a dualistic organization. Drawing on a wide range of methodological approaches and theoretical frameworks that account for how language users mentally represent, process and produce linguistic discourse, the studies in this volume provide a critical examination of dualistic approaches to language and cognition and their impact on a number of fields. The topics range from formulaic language, the study of reasoning and linguistic discourse, and the lexicon-grammar distinction to studies of specific linguistic expressions and structures such as pragmatic markers and particles, comment adverbs, extra-clausal elements in spoken discourse and the processing of syntactic groups"--
The brain and the mind behind grammar : dualistic approaches in grammar research and (neuro)‍cognitive studies of language / Alexander Haselow and Gunther Kaltenböck -- Familiar phrases in language competence : linguistic, psychological, and neurological observations support a dual process model of language / Diana Van Lancker Sidtis -- Dual process frameworks on reasoning and linguistic discourse : a comparison / Bernd Heine, Tania Kuteva and Haiping Long -- Language activity in the light of cerebral hemisphere differences : towards a pragma-syntactic account of human grammar / Alexander Guryev and François Delafontaine -- Dual processing in a functional-cognitive theory of grammar and its neurocognitive basis / Kasper Boye and Peter Harder -- Dichotomous or continuous? : final particles and a dualistic conception of grammar / Katsunobu Izutsu and Mitsuko Narita Izutsu -- The semantics, syntax and prosody of adverbs in English : an FDG perspective / Evelien Keizer -- Formulaic language and discourse grammar : evidence from speech disorder / Gunther Kaltenböck -- Local and global structures in discourse and interaction : linguistic and psycholinguistic aspects / Alexander Haselow -- Agreement groups and dualistic syntactic processing / László Drienkó.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on November 12, 2020).
eBooks on EBSCOhost
Keywords: Psycholinguistics; Cognitive grammar; Psycholinguistics; Psycholinguistique; Grammaire cognitive; psycholinguistics; LANGUAGE ARTS & DISCIPLINES / Linguistics / Psycholinguistics; Cognitive grammar; Psycholinguistics; Electronic book